Víctimas de contaminación por armas frente a la Ley 1448 de 2011: avances, retos y dificultades (2014)
After Afghanistan, Colombia has the highest number of Weapons Contamination victims in the world, and if today the peace agreements were signed, it is estimated that it may take decades or even centuries to eradicate the problem. Consequently, the aim of this conference is to propose a legal, political and practical analysis of the situation of the victims related to this phenomenon in the framework of the Law 1448 of 2011. To fulfil this purpose, the authors will rely on fieldwork as well as national and international research experiences. The methodology will consist in adopting a comparative approach with other countries affected in order to highlight the achievements and the complexities of a holistic approach to the victims of Weapons Contamination in Colombia.